Obesity Indices in Women with Breast Cancer in Cauca, Colombia - Molano-Tobar, Nancy Janneth (2023)
Introduction: Obesity has become a problem that accentuates cancer processes. So the objective was to identify the level of obesity through adiposity indices in women with breast cancer in the department of Cauca-Colombia. Material and Methods: A correlational descriptive study with 126 women diagnosed with breast cancer. The measures for the analysis of body adiposity were the conicity index, body adiposity, abdominal volume, and the CUN BAE equation, body mass index, waist and hip circumferences. The data collected were processed in SPSS, obtaining measures of central tendency and dispersion, such as the Pearson statistic with a significance of p< 0.05 and the Receiver Operating Characteristic (ROC) curve to determine the sensitivity and specificity of adiposity tests, considering ethical and legal aspects. Results: 31.78% of women evaluated presented type IIb cancer. Invasive cancer in axillary lymph nodes, with menarche ages 13.50±2.33 years. An overweight average was observed according to a BMI of 26.91±4.87 Kg/m2. Concerning the waist circumference (46.02%) and the ICC (58.72%), they did not show risk in these variables. Very high positive correlations were identified between waist circumference and adiposity indices (R=0.992), conicity index (R=0.858), and WHR (R=0.845). Conclusions: It was possible to establish that a high percentage of women with breast cancer were overweight, identifying risk situations related to the fat accumulated around the waist, which is related to other adiposity indices. The tool identified as useful corresponded to the index of conicity with statistical significance.